Kajian Faktor Penentu Kesejahteraan Petani Kelapa: Pendekatan Regresi Logistik Ordinal - Winarti, Lili; Permadi, Rokhman (Universitas Galuh, 2024)
One of the critical issues that are still being hotly discussed is farmers' welfare, especially smallholders. The agricultural sector's contribution to the economy is not directly proportional to most farmers' welfare levels, especially in Indonesia. This research is intended to answer the question of the determinant factors that determine the level of welfare of coconut farmers. Purposive Sampling was used to determine Pematang Village, Seruyan Hilir District, Seruyan Regency, as the research location with 60 respondents determined by the Snowball sampling method. The level of welfare of farmer households was analyzed by descriptive analysis, while the determinants of smallholders' welfare were analyzed using ordered logistic regression. The results showed that the determinant factors that affect the welfare of small coconut farmers are land size, ownership of transportation and the amount of production. The results of this study suggest that to improve the welfare of small coconut farmers, a policy related to increasing coconut productivity and easy access to transportation advice is needed.